- #1

Chaz706

- 13

- 0

My brain is truly fried.

I know this:

[tex] \int e^u du = e^u +C [/tex]

But what do I do if I get this:

[tex] \int ae^a^u du [/tex] ? Assuming a is a non-zero constant?

EDIT: Never mind! I figured this out backwards.

[tex] \frac {d}{du} e^a^u = ae^a^u du[/tex]

Thus

[tex] \int ae^a^u du = e^a^u [/tex]

I know this:

[tex] \int e^u du = e^u +C [/tex]

But what do I do if I get this:

[tex] \int ae^a^u du [/tex] ? Assuming a is a non-zero constant?

EDIT: Never mind! I figured this out backwards.

[tex] \frac {d}{du} e^a^u = ae^a^u du[/tex]

Thus

[tex] \int ae^a^u du = e^a^u [/tex]

Last edited: